KECANDUAN GADGET DAN KETERAMPILAN SOSIAL PADA REMAJA DI SMA PGRI I PADANG - Sidaria Sidaria (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
Social skills are very important for teenagers in helping social interaction. Low social skills canlead to poor teenagers to interact effectively with the environment. One of the external factorsaffecting social skills is the advancement of gadget technology where the current phenomenon ofadolescents tend to be addicted to gadgets. The purpose of this study to determine the relationshipof gadget addiction with social skills in adolescents class X & XI in Senior High School PGRI IPadang 2017. This type of research is analytical with cross sectional approach. The population inthis study amounted to 311 people with sampling technique that is proportional random samplingof 76 samples. The research was conducted on July 6, 2017. Data analysis was done by univariateand bivariate statistic test using chi-square with 95% confidence α = 0,05. The results of the studyfound that 55.3% of respondents have poor social skills, adolescents who are addicted to highgadget as much as 52.6%. From the statistical test results showed p value = 0.042 (p <0.05).Baced on these results it can be concluded that there is a relationship between gadgetaddiction with social skills.Key words: Gadget addiction, Social Skills, Teenagers